Health assets among refugees in Australia: a systematic review - Angela Dawson; Evelyn Adjei-Mensah; Andrew Hayen; Sally Nathan; Anita Heywood; Abela Mahimbo; Heidi Merrington; Claire Rogers (BMC Public Health, 2025)
Abstract Background A health assets-based approach seeks to identify health-promoting or protective factors across multiple levels. Evidence of the health assets of refugees at the individual, family, and community levels in Australia is scarce. We aimed to synthesise current evidence from Australia to identify refugee health assets and explore how they influence health and well-being. We explored existing strengths that can be harnessed to ensure sustainable, equitable, and culturally responsive health interventions. Methods We systematically reviewed qualitative and quantitative observational and experimental Australian studies. We searched MEDLINE/PubMed, EMBASE, CINAHL, psych INFO, Web of Science Core Collection and SCOPUS, and used Covidence software for screening and collating articles. We adapted a health assets model for this study using four intersectoral domains and applied it to data extraction and qualitative content analysis. Findings Twenty-nine observational studies were included in this review. Studies reported a relationship between health assets and improved physical, mental, and social well-being of refugees resettled in Australia. A sense of belonging and identity, resilience, acculturation, and well-being most frequently intersect with social capital. This was built through engagement with family and friend networks, participation within cohesive and friendly cultural and host communities, and involvement with religious and educational organisations. Access to education, employment, and community-based activities positively impacted the well-being of refugees. Conclusion A health assets model is a valuable approach to examining protective factors. Refugee social capital and connectedness are strongly linked to resilience, acculturation, health, and well-being. Further research is needed using participatory assets mapping to examine the effects of co-produced interventions that harness the assets of diverse refugee groups to improve health and well-being.